The Effect of CEO on Bank Efficiency: Evidence From Private Commercial Banks - Khan, Israr; Mansi, Wang; Lin, Kuen-Lin; Liu, Chi-Fang; Suanpong, Kwanrat; Ruangkanjanases, Athapol (Frontiers in Psychology, 2021)
The main purpose of this study is to analyze the effects of CEO Key attributes on the financial performance of banks. Current literature gives little attention to the critical characteristics of CEOs. Therefore this paper explores the effects of CEOs' critical characteristics, such as education, experience, nationality, military background, and political connectedness, on the financial (return on assets) performance of listed private commercial banks in Pakistan. This research sample includes 20 private Commercial Banks of Pakistan and uses Secondary data that has been derived from 2011 to 2020, which contains 200 sample observations. This paper uses the Fixed effect model, Normality test, Breush-pagan, white test, multi-collinearity, and Augmented Dickey-Fuller Test to investigate the study hypotheses. The main results revealed that CEO Military background and political connectedness significantly and positively affected bank financial performance. It is also found that the CEO's education and Experience significant and positive relationship with bank profitability. In contrast, the CEO's nationality has no significant relationship with the Bank's financial performance.